Peran Motivasi Kerja, Kepuasan Kerja, dan Komitmen Organisasi dalam Meningkatkan Kinerja Karyawan Perum Bulog Kantor Cabang Surabaya - Bayu Aji Nugroho; Krido Hary Gunawan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the role of work motivation, job satisfaction, and organizational commitment in improving employee performance at Perum BULOG Surabaya Branch Office. The research uses a quantitative explanatory approach with a saturated sampling technique involving 72 employees as respondents. Primary data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 25. The results show that work motivation has a positive and significant effect on employee performance, indicating that motivated employees tend to demonstrate higher productivity and responsibility. Job satisfaction is also proven to significantly influence performance, reflecting that employees who feel satisfied with their work conditions, compensation, and relationships are more likely to achieve better work outcomes. Furthermore, organizational commitment shows a significant positive effect on employee performance, highlighting the importance of emotional attachment and loyalty to the organization. Simultaneously, work motivation, job satisfaction, and organizational commitment contribute substantially to explaining variations in employee performance. These findings emphasize that psychological and attitudinal factors play a strategic role in enhancing employee performance and should be considered as a priority in human resource management practices within public sector organizations.